Evaluasi Mutu Pelayanan Kefarmasian Terhadap Kepuasan Pasien Di Apotek - Lestari, Kartika Ayu; Wahyono, Djoko; Hapsari , Indri (Syntax Literate, 2025)
The purpose of this article is to review and analyze various scientific literature related to the relationship between the quality of pharmaceutical services and patient satisfaction in pharmacies. The methodology used in this article is a narrative literature study of a number of national and international scientific publications published in the last five to ten years. Literature sources are obtained from databases such as Google Scholar, PubMed, ScienceDirect, and Garuda Portal. The inclusion criteria include articles that contain discussions about pharmaceutical service quality indicators, patient satisfaction aspects in community pharmacies, and studies that use quantitative and/or qualitative approaches. This article examines the dimensions of service quality based on the SERVQUAL framework (tangibles, reliability, responsiveness, assurance, and empathy) as well as special aspects of pharmaceutical services such as pharmacist involvement in therapeutic communication, drug use education, and time and queue management. The results of the review showed that there was a significant relationship between the quality of pharmaceutical services and the level of patient satisfaction. The dimensions of responsiveness and assurance, which include the ability of pharmacists to provide fast service and clear and convincing explanations, are the dominant factors in shaping patients' positive perceptions of service quality. The availability and completeness of the drug is also a technical factor that greatly affects satisfaction, where the unreadiness of stock often leads to disappointment. In addition, the physical aspects of the pharmacy such as the comfort of the waiting room, cleanliness, and layout are also important indicators in the patient experience. Pharmacists' interpersonal communication skills and empathetic attitude towards patients are the main determinants in building trust and loyalty relationships between patients and pharmacy services This conclusion confirms that the quality of pharmaceutical services has a significant contribution to the level of patient satisfaction in pharmacies. Therefore, improving service quality must be a strategic priority for pharmacy management, focusing on improving pharmacist competence, service process efficiency, consistent drug availability, and optimization of pharmacy facilities. The practical implications of the results of this study can be a reference for policy makers, pharmacy managers, and pharmacists in designing interventions to improve the quality of services based on patient needs and expectations. Further research is recommended to develop a more comprehensive and contextual pharmaceutical service quality measurement instrument with local conditions.